Natural products and their bioactive compounds: neuroprotective potentials against neurodegenerative diseases - Mohd Sairazi, Nur Shafika; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Hindawi Limited, 2020)
In recent years, natural products, which originate from plants, animals, and fungi, together with their bioactive compounds have been intensively explored and studied for their therapeutic potentials for various diseases such as cardiovascular, diabetes, hypertension, reproductive, cancer, and neurodegenerative diseases. Neurodegenerative diseases, including Alzheimer’s disease, Huntington’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis are characterized by the progressive dysfunction and loss of neuronal structure and function that resulted in the neuronal cell death. Since the multifactorial pathological mechanisms are associated with neurodegeneration, targeting multiple mechanisms of actions and neuroprotection approach, which involves preventing cell death and restoring the function to damaged neurons, could be promising strategies for the prevention and therapeutic of neurodegenerative diseases. Natural products have emerged as potential neuroprotective agents for the treatment of neurodegenerative diseases. .is review focused on the therapeutic potential of natural products and their bioactive compounds to exert a neuroprotective effect on the pathologies of neurodegenerative diseases.